The Value Of Justice In The Determination Of Replacement Heirs From The Perspective Of Maslahah Jasser Auda (Study Of Decision No. 333/Pdt.P/2022/Pa.Purbalingga) - Jawad Muyasar (Judge : Jurnal Hukum, 2024)
The Value of Justice in the Determination of Substitute Heirs from the Perspective of Maslahah Jasser Auda (Study of Decision No. 333/Pdt.P/2022/PA.Purbalingga). Family Law Study Program. Faculty of Islamic Religion, Hasyim Asy'ari University Tebuireng Jombang. This research is motivated by the surrogate heirs who refer to article 185 of the KHI fighting for the rights of heirs who have been abandoned by their parents or heirs who connect them. This kind of situation when viewed from the perspective of Jasser Auda's maslahah is certainly a renewal of thought that needs to be a note of consideration for judges at the Religious Courts. The purpose of writing this research is to understand the implementation of Jasser Auda's maslahah concept in the conceptual problem of substitute heirs which in decision No. 333/Pdt.P/2022/PA.Purbalingga. The researcher uses a type of normative legal research because what will be examined is an official document from the Purbalingga Religious Court Case Number: 333/Pdt.P/2022/PA.Pbg. Using a syar'i approach, namely discussing problems by paying attention to the provisions or rules set out in Islamic syari'at, namely the author is guided by the Compilation of Islamic Law (KHI). The results of this study are in the Purbalingga Religious Court Decision Number 333/Pdt.P/2022/PA. Pbg, the judges decide that there is a substitute heir from a father to his son with legal considerations from the Compilation of Islamic Law which has been established to deal with inheritance issues. In this decision, it is in line with the benefits that must be applied. The judge's consideration, with maslahah Jasser Auda both have the value of enforcing benefit and justice for the heirs who have been determined. Thus, the conceptual maslahah from Jasser Auda in the matter of heirs has actually been upheld by the judges who deal with the problems of heirs.